Jewelry box / Aida Nur Sabrina Adnan - Adnan, Aida Nur Sabrina (2022)
Masjid An-Nur, Tuaran District, is located in the town of Tuaran, Sabah. Has a large area about twice the size of the Sabah State Mosque. The motif, shape, from an artistic line on Tuaran mosque Sabah were transformed into jewelry box design though ideation and development of idea.